New Species of Anomochilus from Borneo (Squamata: Anomochilidae) - Das, Indraneil; Lakim, Maklarin; Lim, Kelvin K. P.; Tan, Heok Hui (Society for the Study of Amphibians and Reptiles, 2008)
A new species of Anomochilus is described from Gunung Kinabalu Park, Sabah, Malaysia (Borneo). The new species is diagnosed from the only two other known species in the genus by the combination of the following character states: SVL to 509 mm; an azygous parietofrontal; paravertebrals 269; transverse body rows 17 : 19 : 17; midventrals 258–261; subcaudals 7–8; dorsum unpatterned dark brown, except for pale flecks, one scale wide, on paravertebral region; large pale blotches absent on dorsum; flanks without light line; and a pair of large pale blotches present on either side of venter. A dichotomous identification key to the three currently known species of Anomochilus is provided. With three species of Anomochilus known for Borneo, the island is the center of diversification of this genus of presumably fossorial and cryptozoic snakes.